1992
DOI: 10.1111/j.1365-4362.1992.tb03519.x
|View full text |Cite
|
Sign up to set email alerts
|

Bullous Diseases in Malaysia: Epidemiology and Natural History

Abstract: The characteristics of three primary bullous diseases, pemphigus, pemphigoid, and dermatitis herpetiformis, seen in this country, probably reflecting this region, are discussed and compared to those reported in the literature in the West. One hundred and forty-eight patients with bullous diseases were seen over a period of 15 years. The criteria for confirmation of clinical diagnosis were the findings of the direct immunofluorescent test. Pemphigus vulgaris was the commonest bullous disease. The incidence of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
53
8
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 6 publications
19
53
8
5
Order By: Relevance
“…A study from Israel including 155 patients reported a female-to-male ratio of 1.5:1 [12]. However, in our study the female-to-male ratio was approximately 1:1 for both PV and PF, which is similar to previous studies from Malaysia and Finland [13,14]. …”
Section: Discussionsupporting
confidence: 40%
“…A study from Israel including 155 patients reported a female-to-male ratio of 1.5:1 [12]. However, in our study the female-to-male ratio was approximately 1:1 for both PV and PF, which is similar to previous studies from Malaysia and Finland [13,14]. …”
Section: Discussionsupporting
confidence: 40%
“…[2][3][4] In the United Kingdom, a regional study estimated an incidence of 1.4 per 100 000 person years. 5 Wide variation in mortality is reported, with one year mortality varying between 6% in the United States and 41% in France.…”
Section: Introductionmentioning
confidence: 99%
“…İnsidansı yaşla birlikte artmakta ve farklı etnik popülasyonlarda değişmektedir [1][2][3] . Dünyanın farklı bölgelerinden BP ile ilgili çok sayıda klinikoepidemiyolojik çalışma bildirilmiştir [4][5][6][7][8][9][10][11][12][13][14] . Ülkemizden de BP ile ilgili 3 farklı epidemiyolojik çalışma bulunmaktadır [15][16][17] .…”
Section: Introductionunclassified